PHYTOCHEMICAL EXAMINATION AND ANTIMICROBIAL ACTIVITY OF VARIOUS SOLVENT EXTRACTS AND THE SELECTED ISOLATED COMPOUNDS FROM ROOTS OF TRAGIA INVOLUCRATA LINN. (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
A large number of medicinal plants have been used for years in daily life to combat diseases, world over. Presently herbs, embodied with due importance in healthcare system, create a herbal renaissance, spread with a greater speed throughout the world. The herbal products today symbolize safety in contrast to the synthetic drugs that are regarded as unsafe to human environment. Population rise, inadequate supply of drugs, prohibitive cost of treatments, side effects of several allopathic drugs and development of resistance to currently used drugs for infectious diseases, have led to increase emphasis on the use of plant materials as source of medicines for a wide variety of human ailments. It is therefore, essential to search for the efficacious plants of medicinal value for better manifestations. In the present study, the fresh roots of young matured plants of Tragia involucrata Linn. were selected for phytochemical and antimicrobial screening to justify the folklore uses of the plant parts in various microbial infections.